Alveolar echinococcosis as a cause of vertebral osteomyelitis and soft tissue infection with recurrent cutaneous fistula formation. (January 2022) - Schmidt-Hellerau, Kirsten; Reiners, Kerstin; Yagdiran, Ayla; Friedrichs, Nicolaus; Fischer, Julia; Fätkenheuer, Gerd; Lehmann, Clara; Jung, Norma
Highlights: Echinococcus multilocularis is endemic in Germany. Cases of alveolar echinococcosis are rare. Unusual clinical presentations in particular may lead to delayed diagnosis. Recurrent sinus tract formation and spondylitis is such a presentation. Abstract: Echinococcus multilocularis is endemic in Germany. However, alveolar echinococcosis is a rare disease. Most commonly the parasite affects the liver, behaving like a malignant tumour. Bones are affected in less than 2% of cases. We report a case of vertebral osteomyelitis accompanied by recurrent cutaneous fistula formation.